Symulacyjna analiza wpływu wyboru kryterium optymalności podziału obiektów na jakość uzyskanej klasyfikacji w algorytmach K-średnich - Najman, Krzysztof (The Influence Analysis of Selection of the Optimum Partitioning Objects Criterion for K-Means Algorithms, 2008)
The paper presents the modification of partitioning means algorithm. There are proposed the application of a nonclassical indices as the inner optimal criterion of the partitioning the objects: index Davies-Bouldin, index Calinski-Harabasz, index Hartigan, trace(W_1B) and det(T)/det(W). On the basis of simulation research critical opinions of quality of partitions that are obtained are maid. There are presented weak and strong points of modified k-maens algorithm. The results are compared with the classical Thorndike's and McQueen's algorithms.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 295-304